Screening for non-classic congenital adrenal hyperplasia in women: New insights using different immunoassays - Nakhleh, Afif; Saiegh, Leonard; Shehadeh, Naim; Weintrob, Naomi; Sheikh-Ahmad, Mohammad; Supino-Rosin, Lia; Alboim, Sandra; Gendelman, Raya; Zloczower, Moshe (Frontiers in Endocrinology, 2023)
Context The 250µg-cosyntropin stimulation test (CST) is used to diagnose non-classic congenital adrenal hyperplasia (NCCAH). The current recommendation is to perform CST when follicular 17-hydroxyprogesterone (17OHP) is 6-30 nmol/L, a cutoff derived from radioimmunoassay (RIA). Recently, enzyme-linked immunosorbent assay (ELISA) has replaced RIA. Objectives We aimed to (1) determine the RIA and ELISA-based 17OHP cutoffs at which CST should be performed, (2) identify predictors of NCCAH. Methods A retrospective study at an Israeli Health Maintenance Organization. Data were retrieved from women with suspected NCCAH, referred for CST during 2001–2020. NCCAH was defined as a stimulated 17OHP >30 nmol/L. Serum 17OHP levels were assayed by RIA from 1/2000-3/2015, and by ELISA from 4/2015-12/2020. ROC curves were generated and optimal 17OHP thresholds were determined. Multivariate analysis was performed. Results CST was performed in 2409 women (1564 in RIA, 845 in ELISA). NCCAH was diagnosed in 4.7% of the RIA group and 7.5% of the ELISA group. The optimal basal 17OHP cutoff values predicting NCCAH were 6.1 nmol/L in RIA (sensitivity=93.2%, specificity=91.7%) and 8.2 nmol/L in ELISA (sensitivity=93.7%, specificity=92.3%). In multivariate analysis, higher basal 17OHP, lower LH: FSH ratio, and oligomenorrhea were predictors of NCCAH in RIA. Higher basal 17OHP, androstenedione, and total testosterone were predictors of NCCAH in ELISA. A lower LH: FSH ratio showed similar trend in ELISA. Conclusions Optimal RIA-based basal 17OHP cutoff was comparable with that recommended in guidelines. The results suggest adopting a higher 17OHP cutoff when using ELISA. LH : FSH ratio improves the negative predictive value of basal 17OHP.